Analysis of the Role of Universities in Supporting Sustainable Growth: the Case in Indonesia - Rini Kurnia Sari; Cecep Hidayat; Stephanie Bangapadang (IAIC International Conference Series, 2021)
Indonesia is predicted to experience a demographic bonus period in 2030. In order for Indonesia to get the maximum benefit from this demographic bonus, the availability of abundant productive-age human resources must be balanced by improving the quality of education and skills. Educated and competitive human resources need to be improved in terms of the number and quality of competitiveness to support sustainable growth. In this research, the authors want to see the role of universities in influencing economic growth. The role of universities can be measured by the number of universities, college enrollment rate and the human development index (HDI). The analysis used in this study is multiple linear regression analysis. The research data used are panel data, data from 34 provinces in Indonesia with the study year 2015 - 2018.